2011
DOI: 10.1177/1040638711425940
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant E-cadherin, β-catenin, and glial fibrillary acidic protein (GFAP) expression in canine choroid plexus tumors

Abstract: Abstract.Expression of E-cadherin and β-catenin has been widely studied in various human and canine epithelial tumors and has been correlated with dedifferentiation, invasiveness, and metastasis. Choroid plexus tumors (CPTs) are of epithelial origin, and the most important prognostic factor in human medicine is the tumor grade. Limited information is available regarding E-cadherin and β-catenin expression in human CPTs, and no information is found in the veterinary literature. In the current study, 42 canine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…12 However, based on histologic criteria more recently, Westworth et al did not meet criteria for atypical CPPs and identified CPCs in up to 64% of cases in dogs. 14 In the same way, atypical CPPs were not identified by Nentwig et al 10 In the current study a high number of neoplasms were classified as atypical CPPs. Certainly contributing to this result is the fact that in the human classification system, (1) the role of the peripheral infiltration is downsized, and (2) the presence of necrotic areas is no longer assumed as an unquestionable index of malignancy.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…12 However, based on histologic criteria more recently, Westworth et al did not meet criteria for atypical CPPs and identified CPCs in up to 64% of cases in dogs. 14 In the same way, atypical CPPs were not identified by Nentwig et al 10 In the current study a high number of neoplasms were classified as atypical CPPs. Certainly contributing to this result is the fact that in the human classification system, (1) the role of the peripheral infiltration is downsized, and (2) the presence of necrotic areas is no longer assumed as an unquestionable index of malignancy.…”
mentioning
confidence: 56%
“…However, these efforts have produced contradictory results. 10,12,14 Normal adult choroid plexus strongly expresses E-cadherin 5 and N-cadherin 9 as adhesion molecules. E-cadherin is found mainly in the epithelia, where it promotes tight cell-cell associations known as adherens junctions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, diagnosis of brain biopsies, which may lack overall architecture and histologic pattern, can be difficult. Although CPTs arise from the choroid plexus epithelium, cytokeratin immunoreactivity in canine tumors has been reported to be variable with at least 1 study indicating only a small number of cases immunoreactive to wide-spectrum cytokeratin; however, immunoreactivity of these are either variably or not specific to CPTs.…”
mentioning
confidence: 99%
“…Although CPTs arise from the choroid plexus epithelium, cytokeratin immunoreactivity in canine tumors has been reported to be variable with at least 1 study indicating only a small number of cases immunoreactive to wide-spectrum cytokeratin; however, immunoreactivity of these are either variably or not specific to CPTs. 3,5,9 In human samples of CPTs, tissue microarray analysis has identified several candidate genes that are specific to choroid plexus and allow for differentiation from metastatic carcinomas. 2 One of these diagnostic markers is the inward rectifier potassium (K + ) channel Kir7.1, also known as inward rectifier potassium channel 13 or potassium inwardly rectifying channel, subfamily J, member 13.…”
mentioning
confidence: 99%